(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article aimed to examine the elaboration of melancholy in Moço em Estado de Sítio, by Oduvaldo Vianna Filho, written shortly after the 1964 military coup. Through the analytical reading of this dramaturgical production, it was analyzed how the tensions and disagreements that permeate the central characters, as the narrative structure itself, delineate a certain type of melancholic diagnosis of the country in front of the social fracture and the malaise arised from the military regime, as well as the stagnation of a generation of intellectuals and artists who were similarly besieged after 1964.